1996
DOI: 10.1016/s0022-5347(01)66130-5
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Transrenal Electro-Incision of Ureterointestinal Anastomotic Strictures: Long-Term Results and Comparison of Fluoroscopic and Endoscopic Guidance

Abstract: Combined endoscopic and fluoroscopic guidance is preferable to fluoroscopy alone. The technique is simple if the endoscope is inserted retrograde. Long-term results are satisfactory and we believe that incision should be the initial approach to strictures of uro-digestive anastomoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(13 citation statements)
references
References 10 publications
0
10
0
3
Order By: Relevance
“…Alternatively, the endoscopic technique including electroincision of the anastomotic stricture has been described by Cornud et al [5]. The holmium:YAG laser is an ideal tool for performing endoureterotomy.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the endoscopic technique including electroincision of the anastomotic stricture has been described by Cornud et al [5]. The holmium:YAG laser is an ideal tool for performing endoureterotomy.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 4-8% of intestinal urine diversion procedures after radical cystectomy are complicated with ureterointestinal strictures [2][3][4]. Ureteroileal anastomosis strictures are usually asymptomatic and may cause significant renal damage before discovered.…”
Section: Discussionmentioning
confidence: 99%
“…Leisinger and Deyhle were the first to present a successful endoscopic incision of a stenosis at the ureteroileal anastomosis using an electric wire loop [23], while Cornud et al reported a success rate of 71% when the stricture was incised using a papillotome [3]. Poulakis et al utilized a cold-knife incision technique of the stricture at the ureteroileal anastomosis in a series of 40 patients, and reported a success rate of 60.5% with a mean follow-up period of 38.8 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meretyk et al 67 and Cornud et al 68 were first to describe the use of a cutting electrode for treatment of ureteroenteric anastomotic strictures. However, their technique was limited by the need for specialist endoscopic equipment and for urologists with expertise in interventional uroradiological techniques.…”
Section: Endoureterotomymentioning
confidence: 99%